L-shaped nonlinear relationship between magnesium intake from diet and supplements and the risk of diabetic nephropathy: a cross-sectional study - Du, Jia; Zhu, Xuetong; Li, Ze; Sun, Qi; Sun, Miao; Guan, Heyuan; Xu, Jiancheng (Frontiers in Nutrition, 2025)
Background and objectivesGiven the ongoing controversy regarding the relationship between magnesium and diabetic nephropathy (DN), this study systematically evaluate the association between total magnesium intake from both dietary and supplemental sources and the risk of DN, and further explore its potential nonlinear dose–response pattern and threshold effect.MethodsData were from the National Health and Nutrition Examination Survey 2007–2018. A multi-step analytical strategy was adopted: (1) confounders were selected using variance inflation factor and Boruta feature selection algorithm; (2) weighted multivariable logistic regression assessed the association between magnesium intake and DN; (3) restricted cubic splines (RCS), generalized additive models (GAM), and curve fitting were used to evaluate nonlinear dose–response trends; (4) piecewise regression identified potential thresholds; (5) subgroup analyses examined interactions across age, gender, BMI, hypertension, and cardiovascular disease.ResultsA total of 3,355 participants were included (DN group: n = 1,295; non-DN group: n = 2,060). The magnesium intake among DN patients was significantly lower than that of non-DN patients [300 ± 171 mg/day vs. 329 ± 161 mg/day, p < 0.001]. After adjusting for confounders, each standard deviation (SD) increase in magnesium intake was associated with a 19% reduction in DN risk (OR = 0.81, 95% CI: 0.73–0.89). Compared with the lowest quartile of magnesium intake (Q1), the highest quartile (Q4) showed a significantly lower risk of DN (OR = 0.54, p < 0.001). RCS analysis suggested an L-shaped nonlinear association (nonlinearity-p = 0.003), which was further supported by GAM results. Piecewise regression analysis identified a turning point at 345.00 mg/day. Below this value, higher magnesium intake was significantly associated with lower DN risk; above this threshold, the protective effect plateaued. No significant interactions were found in the subgroup analyses.ConclusionTotal magnesium intake was inversely associated with DN risk, with a threshold identified at 345.00 mg/day. Below this level, increases in magnesium intake were significantly associated with reduced DN risk, whereas above this level, additional magnesium intake was not significantly associated with further reductions in DN risk. These findings provide new epidemiological evidence to inform magnesium intake recommendations and DN prevention strategies.